STRATEGIES FOR DEVELOPING COMMUNICATIVE AND CULTURAL COMPETENCE OF ECONOMICS STUDENTS THROUGH LITERARY TEXTS - Tukhtarova, Iroda (International Conference on Social Sciences & Humanities, 2026)
This article investigates the pedagogical, linguistic, and cultural significance of incorporating literary texts into English language instruction for economics students. Based on communicative and task-based teaching approaches, the study analyzes how authentic literary materials contribute to vocabulary expansion, increase cultural awareness, and facilitate the contextual learning of grammar while simultaneously developing higher-order thinking skills, including analysis, synthesis, and critical evaluation. The research indicates that literary texts function as effective educational resources that encourage emotional involvement, enhance inferential thinking, and promote a deeper understanding of socio-cultural meanings conveyed through language. Furthermore, the study emphasizes that literary excerpts related to economic topics can enrich ESP (English for Specific Purposes) instruction by offering meaningful contexts for mastering professional terminology and conceptual knowledge. The findings suggest that literature not only strengthens students’ language proficiency but also supports their intellectual development, communicative confidence, and academic preparedness. Overall, literary texts can be regarded as versatile and effective tools for developing linguistically competent, culturally aware, and critically thinking learners in higher education..